Endovascular therapy after acute ischaemic stroke—Experiences and needs of relatives. Issue 5 (19th September 2018) - Sørensen, Kristina Eiskjær; Dreyer, Pia; Rasmussen, Mads; Simonsen, Claus Z.; Andersen, Grethe
Abstract: Aims and objectives: To explore the experiences and needs of relatives being part of the endovascular therapy (EVT) pathway. Background: Ischaemic stroke is the third leading cause of death and the most common cause of acquired disability among adults in the Western world. The most recently approved treatment for major stroke is EVT. Removing the arterial occlusion has proven to be the best predictor of outcome. While patients are treated, relatives are left waiting. Facing the massive shock of their loved ones having a stroke may cause emotional turmoil and leave relatives with various needs. No previous studies have explored experiences and needs of relatives who are part of an EVT pathway. Design: A qualitative design using a phenomenological–hermeneutic approach. Methods: Semi‐structured interviews and participant observations were carried out. Data were collected from April 2016–January 2017. Data were analysed using Ricoeur's theory of interpretation, capturing meaning and ensuring comprehensive understanding. Results: Four themes emerged are as follows: (a) The first phase—shock, chaos and feeling paralysed; (b) the all‐important information—sharing is pivotal; (c) professional loving care—being seen and heard by caring health professionals; and (d) adjusting to new roles. One essential finding that emerged across all themes was relatives' constant need for care, for support and for health professionals to "be there." Conclusion: Relatives need support and care during the entire EVT pathway. They tend to be modest and ignore their own needs. Relatives who experience chaos, fear and worry need to be met by professionals with real presence. Relevance to clinical practice: These findings will be used as a foundation for development of local structures and policies that should provide knowledge and ensure a consistent and proactive approach to meet the needs of the relatives in a timely and efficient manner.